PRENATAL ATTACHMENT AND ANXIETY DURING THE FINAL TRIMESTER OF PREGNANCY IN EARLY PARENTHOOD. A PRELIMINARY STUDY - Regina Rodrigues, Ana; Pérez López, Julio; Brito de la Nuez, Alfredo G. (Anales de Psicología / Annals of Psychology, 2004)
This work analyses the existing connections between the degree of satisfaction in the couple-relationship, the anxiety level of expectant parents and levels of prenatal emotional attachment. Nine couples participated (age range in women 26 to 42 years; age range in men 30 to 40 years) and completed the Inventory of Situations and Responses to Anxiety (ISRA) (Tobal y Cano Vindel, 1994), the Questionnaire on Areas of Compatibility-Incompatibility in Couples (GSP) (Serrat, 1980); and the Questionnaire for Assessment of Prenatal Emotional Attachment (EVAP) (Lafuente, 1994). A simple regression analysis was carried out and results indicated that the degree of satisfaction in the couple (GSP) did not show a significant relation to levels of prenatal emotional attachment (EVAP) whereas anxiety levels among the women showed a significant connection to this attachment.